A critical te Tiriti analysis of the New Zealand cancer action plan 2019–2029. (December 2020) - Came, Heather; Kidd, Jacquie
Highlights: The NZ Cancer Control Action Plan is assessed as fair in its te Tiriti compliance. Health policy needs to engage with Indigenous knowledge. Over 17 years cancer control policy has become more te Tiriti compliant. Critical te Tiriti Analysis is a potential accountability tool for Indigenous health. Abstract: There are systemic health inequities, including around cancer between Māori (the Indigenous peoples of Aotearoa) and non-Māori. These inequities place a huge social, cultural, spiritual, emotional, and economic burden on Māori as they navigate the intergenerational legacies of colonisation. The New Zealand Cancer Action Plan 2019–2029 is one of the first major health policy documents published since the Waitangi Tribunal released the landmark WAI 2575 report. This report found widespread non-compliance of health policy in relation to te Tiriti o Waitangi . The New Zealand Ministry of Health have committed to addressing this non-compliance and proactively addressing ethnic health inequities. This study applies a Critical te Tiriti Analysis over the Cancer Plan to review its te Tiriti compliance in a new political environment where te Tiriti compliance is a priority. The analysis involves a five-phase analysis from i) an initial orientation, ii) a close examination, iii) a determination, followed by iv) suggestions how to strengthen the policy and a v) Māori final word. We rated the Cancer Plan as fair (level 2 of a 4 point scale) on te Tiriti compliance which was an improvement over the 2003 Cancer Strategy. Centring mātauranga Māori (Māori knowledge), kaupapa Māori (Māori philosophical approaches) and Māori public health would have strengthened the Plan. Given the consistent failure of the health system to uphold its te Tiriti responsibilities, the absence of detail makes it difficult for the Crown to be held to account. Indigenous peoples across the world have a right to health. Tools such as Critical te Tiriti Analysis are one way to ensure governments are held to account for their performance.